Variations in Electrolytes Level After Del-Nido Cardioplegia Administration in Patients Undergoing Congenital Heart Defects Surgery - Noor, Mah; Asghar, Muhammad Imran; Umer, Muhammad Shoaib; Azad, Naseem; Khalil, Hafsa; Chachar, Zara (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the variation (increase or decrease) in Electrolytes level after del-nido cardioplegia administration in patients undergoing on pump congenital heart defect surgery. Study Design: The design used in this study was descriptive cross-sectional. Place and Duration of Study: The study was carried out at Pediatric Cardiac Surgery Department of Armed Forces Institute of Cardiology in Rawalpindi, Pakistan from Oct 2021 to Dec 2021. Methodology: Patients undergoing congenital heart surgery were the subject of interest in this study. The sample size was 147.Non-probability consecutive sampling technique was used. Patients undergoing on pump Congenital Heart Surgery, patients with age < 30 years, patients of both gender were included in our study. Patients with surgery of multiple stages (abdominal surgery, palliative surgery), Emergency patients, Chronic renal failure patients, Re-do operations were excluded from our study. Results: Sample size was 147 with anticipated percentage 10.7% having 78(53.1%) males and 69(46.9%) females who underwent congenital cardiac surgery. Statistical test was applied and results are significant. There was significant difference in the means of electrolyte levels after administration of Del-Nido Cardioplegia (p-value <0.05). Conclusion: Our study concluded that after Del-Nido Cardioplegia administration, imbalance in electrolytes levels (Sodium,Potassium, and Calcium) occur which causes hyperkalemia, hypernatremia and hypercalcemia. Prolonged cardiopulmonary bypass time and cross clamp time are risk factors for increased del-nido cardioplegia administration.